Emergence and Convergence of Information and Communication Technology in Higher Education - kumar, Sree; Acharjya, D. P. (Gyan Management Journal, 2007)
The emergence and convergence of comrmmication and information technology is opening up new opportunities and challenges to higher education worldwide. In the new millennium, educational quality is the key and instructional technology will play a pivotal role in providing the quality education. The growing number of candidates interested for life long learning, the conventional text books failing to update knowledge in time will compel the education system to rely heavily on ICT (Information and Communication Technology) to provide the quality ducation through various modes like distance learning, virtual universities etc. This paper reviews various perspectives of higher education and the role of ICT expected.